Student’s Ability and Factors to Use Gerund and To Infinitive Case Study: Indonesian EFL Learners in University Level - Rina Husnaini Febriyanti (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2019)
Mastering grammar seems very challenging for English foreign language learners. Learning grammar constructions that they do not find or have different system to their first language bring some consequences. One of them is on learning about gerund and to infinitive. The objectives of this study are to describe the ability on mastering gerund and infinitive form and to analyze the factors affecting them to learning its form. This study used descriptive method. The respondents of this research were the students who took English Structure subject on second year of Indraprasta PGRI University Jakarta. Moreover, the data was collected through the instruments, and they were test and questionnaire. The data was analyzed descriptively, and it was tabulated and calculated. Next, it was presented in percent form. After analyzing the data descriptively, the research result is the ability of the students on mastering the using of gerund is on very poor range that is 41.82% (23 out of 55), in other words, it can be said that more than half respondents were still in low understanding of gerund, in the same time, mastering the using to-infinitive form is on very poor range that is 36.36% (20 out of 55), or it can be said that the respondents were still low in understanding of to infinitive. The factors affecting them were being passive, lack of motivation, slow learning, less practice in doing exercises, poor of literature, and not learning from the mistakes. These findings may encourage the lecturer of English Structure to find out more ways to improve student’s ability especially on using gerund and to infinitive for Indonesian EFL Learners in University level.